New user interface using a single Braille cell approach - Schmidt, Marcelo Bernart; Metzger, Luiz Gustavo; Mortimer, Robert; Garcia Ramirez, Alejandro Rafael (Informática na educação teoria & prática, 2017)
Access to information is usually a challenge for visually impaired people. Auditory and the Braille systems become an ally for them, allowing access to knowledge, identification of products and places, among others uses. However, technologies for printing and reading in Braille are expensive, constraining its dissemination and use. This work presents a Braille reading system, based on a single cell’ approach, designed for computer interactions. The single Braille cell concept is closely related to fingertip’s physiology and it is based on a static reading. The designed computer interface took into account accessibility standards preconized by IBM. The system features voice recognition, auditory feedback and provides two operation modules: training and reading. The system was evaluated by three blind participants with different kinds of Braille’ knowledge and different computer’s skills. The results promises an efficient way to learn Braille using the single Braille cell concept.